Directions of harmonization of the main principles of domestic administrative and legal science with European integration requirements (Bulletin of Kharkiv National University of Internal Affairs, 2022)
It has been noted that today the process of integration of national legislation into the unified European legal system is of unprecedented importance for many spheres of Ukrainian society, and most of all for the legislative basis that regulates legal relations between the state in general and society and citizens in particular. It has been emphasized that for the above reason, the process of European integration of national legislation has the most significant impact on administrative and legal science, since this branch of law is the most important regulator of social relations in the field of public administration, specifies and regulates the rules of operation, organization of activities and legal status of public authorities, and also establishes the rights and obligations of citizens and public organizations in the specified sphere.It has been established that an important role in the functioning of all legal branches is played by the basic, objectively determined foundations on which the activities of public authorities are built. At the same time, their functioning should be included in the system of legal acts that determine the regulatory limits of administrative law. It has been emphasized that the basis of research in the specified field of law should be the actualization and systematization of the above-mentioned principles.It has been summarized that the directions of adaptation and harmonization of the main provisions of the national administrative and legal science with the European integration requirements set by the partner countries to Ukraine as a candidate for accession to the European Union should, first of all, be implemented through the prism of revision of the scientific paradigm of the basic principles of administrative law in general and public administration in particular. The above-mentioned approaches are aimed at demonstrating to the world community the steady rise of Ukraine as a legal, democratic state, ensuring effective cooperation of state institutions and civil society, guaranteeing commitment to the principles of the rule of law, as well as maintaining the proper level of functioning of the law enforcement mechanism of our country.